Institutional Sustainability and Quality Enhancement in Cambodian Higher Education: A Mixed-Methods Inquiry - Prak Polla; Phim Monisetha (jfpublisher, 2026)
This study examined how Cambodian higher education institutions (HEI) enhance their educational development in terms of quality improvement and institutional sustainability. A mixed-method was employed in the study. First, a quantitative survey with 385 participants using questionnaires was done, followed by an in-dept interview was conducted with 24 participants who are leaders and managers from 12 HEIs in Phnom Penh. The descriptive statistics and thematic analysis were used to analyse quantitative and qualitative data respectively. Findings from the study show that the strongest factor contributing to HEI sustainability is “sustainability-related quality practices” with (48.8%) agreed, followed by “teaching methods” (57.4%), “digital capabilities” (44.9%), “quality assurance” (46.5%), governance and management” (51.8%). The findings also show the main constraints faced by the HEIs currently that “Financial and infrastructural” was the major obstacles agreed by 45.5% respondents followed by “shortage of digital systems” (55.1%). Moreover, participants expressed their views in the interview that there was a concern on the “workload of staff”, “environment pressures”, “ICT/infrastructure expenses”, and “autonomy” which contribute to the quality improvement of the HEI and as a result affects the HEI sustainability. The study also discusses some controversies issues for instance: (i) senior leadership commitment versus faculty/department implementation, (ii) professional development versus regular and limitation of access.” Findings from the study contribute to the HEI policy development.